Associations of early age-related macular degeneration with ocular and general parameters: the central India eyes and medical study - Jonas, Jost B. (Acta ophthalmologica, 2012)
Abstract. Purpose: To assess associations between age-related macular degeneration (AMD) and ocular and general parameters. Methods: The Central India Eye and Medical Study, a population-based study performed in rural Central India, included 4711 subjects (aged 30+ years) out of 5885 eligible subjects (response rate: 80.1%). Fundus photographs were assessed using the Wisconsin Age-Related Maculopathy Grading system. Results: Fundus photographs were available for 4542 (96.4%) subjects. Early AMD was present in 215/4542 subjects (4.7 ± 0.3%), and late AMD was detected in 8/4542 (0.2 ± 0.03%) subjects. After adjustment for age, prevalence of AMD was significantly associated with hyperopic refractive error (p = 0.001), shorter axial length (p = 0.01), and higher corneal refractive power (p = 0.02). Each dioptre increase in hyperopic refraction or each millimetre decrease in axial length was associated with a 15% [odds ratio (OR):1.15; 95% confidence interval (CI): 1.06, 1.24] and 19% (OR: 0.81; 95%CI: 0.69, 0.95) increased probability of early AMD, respectively. AMD was not significantly associated with blood pressure, serum concentration of cholesterol, glycosylated haemoglobin Hb1Ac, high-density lipoproteins and postprandial glucose, gender, level of education, any parameter of smoking, alcohol consumption, psychiatric depression or of daily activities, anterior chamber depth, lens thickness, intraocular pressure, size of the optic disc, neuroretinal rim and parapapillary atrophy, nor amount of nuclear cataract and status after cataract surgery. If the statistical analysis was adjusted for age and refractive error, age-related macular degeneration was marginally significantly associated with a low intake of fruits (p = 0.06). Conclusions: Hyperopia (and short axial length) besides age was the single most important associated factor for AMD in adult Indians.
Gesehen am 28.08.2018
First published: 23 January 2012